Analysis Of Fomo Lifestyle and Consumer Behavior Of Gen Z Students Towards Viral Goods - Dewi Sinta Puspitasari; Dynda Prista; Sudarmiatain Sudarmiatain (Universitas 45 Surabaya, 2025)
The phenomenon of Fear of Missing Out (FoMo) has become more prevalent with the increasing use of social media among students. FoMo can drive individuals to follow the latest trends, including purchasing viral items. This study aims to analyze the influence of FoMo lifestyle on students' purchasing decisions of viral products in Malang City. The research uses a qualitative approach with case study interviews. The results show that FoMo lifestyle has a strong influence on purchasing decisions of viral products. The main factors affecting these decisions include social pressure, exposure to social media content, and the desire for social validation. Additionally, it was found that students with a higher level of FoMo tend to make impulsive purchases and give less consideration to the functional aspects of the items they buy.